Anestesia de canídeos do cerrado in situ: avaliação de protocolos a partir de dados coletados a campo - Rizardi, Mayra Bertolo (Universidade Federal de São Carlos, 2025)
Chemically restraining wild canids in situ is a part of conservation efforts for these species, since its capture and manipulation for biological sampling and telemetry collars setup are essential to the studies. No studies bring robust data comparing anesthetic protocols, specifically concerning the Cerrado species. Founded in 2009, the Cerrado Mammals Conservation Program (PCMC) has been developing in situ research at Minas Gerais and Goiás states and has been gathering notable experience in Cerrado carnivores capture and anesthesia, adding up to more than 400 chemical restraint procedures and these are the records that hold the foundation of the present work that aimed to access the chemical restraint protocols used in Crab-eating fox (Cerdocyon thous), Hoary fox (Lycalopex vetulus) and Maned wolf (Chrysocyon brachyurus) captured by the PCMC from 2008 to 2023. We built a database based on PCMC field anesthesia records. A spreadsheet was developed for each species and exporte do R Studio software to analyze protocol dosage, recumbency, latency, immobilization, initial recovery, supplementation duration, antagonism recovery, recumbency rate, heart rate, respiratory rate, rectal temperature and depth of anesthesia. The database comprised a total of 183 procedures with C. thous, 117 with L. vetulus and 21 with C. brachyurus. All the anesthetic protocols analyzed provided suitable depth of anesthesia for basic handling and sampling. Ketamine-midazolam-butorphanol (KMB) is the most numerous recorded protocol for the three species with times of induction, immobilization and recovery suitable for field procedures, and proven stability of vital signs and anesthesia depth. Anesthesia supplementation was very often, but knowing dosages, time of action and securing peripheral venous access makes it possible to prepare in advance. Ketamine-midazolam-butorphanol-xylazine (KMBX) produced longer immobilization time, better muscle relaxation and less need for supplementation in the foxes’ procedures, but the evident presence of arrhythmia deserves further investigation. Ketamine-midazolam-butorphanol-dexmedetomidine (KMBD), despite providing longer immobilization time, great muscle relaxation, fast recovery and the possibility of using antagonists, the marked presence of arrhythmia, sudden awakening and low flow at blood collection brings the necessity of carefully thinking and preparing for this combination. Midazolam-butorphanol-dexmedetomidine (MBD) brings the same disadvantages, but is potentialized by the absence of ketamine, resulting also in temperature consequences. Tiletamine-zolazepam (Z) brings the practicality of usually resulting in low volumes, which is desirable for wild animals’ anesthesia. But it is plainly registered in literature the excitation side effects, demonstrated in this study by the high values of heart and respiratory rates in both foxes. Its prolonged and agitated recovery is another currently known disadvantage, that takes Z off the place of drug of choice for wild canids. Our study provides a level of anesthetic data robustness not yet available in the current literature, hopefully contributing valuable information to support conservation efforts for Cerrado canids.
Anesthesia of Cerrado canids in situ: evaluation of protocols based on field-collected data
Keywords: Canídeos silvestres; Contenção química; Conservação; Raposinha-do-campo; Cachorro-do-mato; Lobo-guará; Wild canids; Chemical restraint; Conservation; Hoary fox; Crab-eating fox; Maned wolf; CIENCIAS AGRARIAS::MEDICINA VETERINARIA::CLINICA E CIRURGIA ANIMAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES